Avaliação da força muscular respiratória e função pulmonar em indivíduos com Diabetes Mellitus Tipo 2 - Oliveira, Luma Zanatta de (2017)
The aim of this dissertation was to evaluate the respiratory muscle strength and lung function of individuals with type 2 diabetes mellitus who participated in a hospital group of Neurology, Endocrinology and Medical Clinic in the city of Passo Fundo, RS. We present in this work a scientific production, whose specific objectives were: to evaluate and compare respiratory muscle strength and pulmonary function between diabetics and control group; analyze the predicted and obtained values of respiratory muscle strength and lung function in both groups; compare the values of respiratory muscle strength and lung function among the groups evaluated; to correlate pulmonary function with the time of diagnosis of diabetes and to compare the Body Mass Index intergroups. The hyperglycemia present in diabetes causes inflammatory processes, because of this the lung is considered a target organ, being more affected by being rich in collagen, elastin and microvascular network. This leads to a compromised pulmonary elasticity and alveolar-capillary network. This production was a prospective cross-sectional study and to analyze the data the wilcoxon and Mann-Whitney tests were used and the significance level was p ≤ 0.05. The sample consisted of 48 participants, of whom 27 had a medical diagnosis of type 2 diabetes mellitus who attended the outpatient clinics, in addition to 21 individuals without diabetes who were part of the control group. The participants were referred to private clinic of Neurology and Neurosurgery Service and the Faculty of Physical Education and Physiotherapy of the University of Passo Fundo. Regarding respiratory muscle strength and lung function, we found that there was no reduction of values obtained in both groups; As compared to expected and obtained values, both groups showed values higher than predicted with a statistically significant difference in maximum expiratory pressure, forced vital capacity and expiratory volume in the first second; The group with diabetes had a mean body mass index of 30.3 ± 5.2, the control group had a mean of 26.8 ± 3.4. According to these results, we understood that there was no relationship between respiratory muscle strength and type 2 diabetes mellitus, because the diabetic patients that we evaluated were in a hospital group with medical care directed to their clinical condition. The abdominal adiposity is considered a risk factor for the development of the disease, which corroborated with our findings. We suggest that more studies analyzing these variables can be under taken in a population that is vulnerable to risk factors, without multidisciplinary approuch.